Mobile Restaurant- An advanced food ordering service via handheld devices - Minh, Nguyen Kong (Universiti Teknologi Petronas, 2006)
Handheld devices provide a means for customers to place and pay for orders on-the-fly in nowadays m-commerce generation. Therefore, the aim of this project is to develop a system that has capability in handling the food ordering service in Universiti Teknologi Petronas (UTP) with the use ofhandheld devices. Currently, the food services in campus are not efficient enough in which customers usually have to wait long time for the food to be prepared when they enter the cafeteria. In addition, customers do not have chance to know in advance the type of food will be available until they physically reach the restaurant. A system targeting on mobile devices is developed to overcome the limitations of the current services - Mobile Restaurant. In chapter 3, author will discuss about the methodology used to develop the system, which is waterfall model consists of five phases: requirement definition, system & software design, implementation &unit testing, integration &system testing, and operation &maintenance. The system prototype consists of three sub systems, which are client application implemented in mobile devices, a SMS notification service, and the web-based service administration. Chapter 4 will introduce the volume of work has been done and discuss on some issues for the implementation ofthe system. The first two sub systems had been completed and tested. The third sub system is under development for future enhancement. As in conclusion, the scope ofthe project has been successfully achieved and it provides a sophisticated system to enhance the restaurant's production and food on time delivery process. _